Implementation of European standards in the activities of local government bodies - Kozin, Anastasiia; Kozin, Serhii (Edelweiss Applied Science and Technology, 2025)
The relevance of the study lies in the need to determine the compliance of local government activities with European standards, as Ukraine's European integration course involves the implementation of a number of tasks, particularly the compliance of such activities with European standards and the decentralization of power. The purpose of the article is to conduct a comprehensive analysis of European standards of local self-government from the perspective of their democratic potential, to determine which of them require implementation in the national legislation of Ukraine, and to propose methods and tools for implementing the latter in the activities of local self-government. The research methodology consisted of methods that enabled the study of European standards of local self-government and the mechanism for their implementation in the national legal system (logical-semantic method for analyzing the essence of European standards of local self-government; modeling, which was used to study trends in the implementation of European standards; analysis, synthesis, and generalization - to determine the advantages of implementing European standards). As a result of the study, the problems of implementing European standards in the activities of local self-government were identified, and the conclusion proposed ways to solve them.